2011
DOI: 10.1097/yic.0b013e3283400d35
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled study of adjunctive ramelteon in ambulatory bipolar I disorder with manic symptoms and sleep disturbance

Abstract: This study evaluated the efficacy and tolerability of ramelteon in ambulatory bipolar I disorder with manic symptoms and insomnia. Twenty-one outpatients with bipolar I disorder by Diagnostic and Statistical Manual of Mental Disorders, fourth edition criteria with mild-to-moderate manic symptoms and sleep disturbance were randomized to receive either ramelteon (N=10) or placebo (N=11) in an 8-week, double-blind, fixed-dose (8 mg/day) study. Ramelteon and placebo had similar rates of reduction in ratings of sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 0 publications
0
45
1
1
Order By: Relevance
“…In this study, ramelteon did not demonstrate efficacy greater than placebo on the primary outcome measure (change in insomnia assessed by 65-item Pittsburgh Insomnia Rating Scale), nor did it have differential effects on manic symptoms or global severity of illness (23). However, it did demonstrate improvement in global rating of depressive symptoms, and no serious adverse events were observed (23). Although this study represents one of the first attempts to conduct a randomized controlled study for insomnia in bipolar disorder, the small sample size (total N=21), as well as the fact that patients were hypomanic, may limit the power of the study to detect benefit over placebo, as well as the generalizability of results to the management of comorbid insomnia in other phases of bipolar disorder.…”
Section: Bipolar Disordercontrasting
confidence: 63%
See 2 more Smart Citations
“…In this study, ramelteon did not demonstrate efficacy greater than placebo on the primary outcome measure (change in insomnia assessed by 65-item Pittsburgh Insomnia Rating Scale), nor did it have differential effects on manic symptoms or global severity of illness (23). However, it did demonstrate improvement in global rating of depressive symptoms, and no serious adverse events were observed (23). Although this study represents one of the first attempts to conduct a randomized controlled study for insomnia in bipolar disorder, the small sample size (total N=21), as well as the fact that patients were hypomanic, may limit the power of the study to detect benefit over placebo, as well as the generalizability of results to the management of comorbid insomnia in other phases of bipolar disorder.…”
Section: Bipolar Disordercontrasting
confidence: 63%
“…McElroy and colleagues assessed the use of ramelteon 8mg nightly versus placebo in outpatients with bipolar disorder experiencing mild to moderate manic symptoms and insomnia (23). During the course of the 8-week study, other medications were continued and left unchanged (except in instances in which a medication required dose reduction for side effect management) (23).…”
Section: Bipolar Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…A small pilot study suggested that adding valnoctamide 600-1,200 mg/day (which is an anticonvulsant analogue of valproate that does not undergo biotransformation to the corresponding free acid and in mice has been shown to be distinctly less teratogenic than valproate) on risperidone was more efficacious against acute mania in comparison with risperidone plus placebo [62]. A pilot study on the usefulness of adjunctive ramelteon against acute mania/mixed was positive [340].…”
Section: Other Agents and Therapeutic Modalitiesmentioning
confidence: 97%
“…Two small clinical trials have recently evaluated ramelteon for sleep disturbance in bipolar disorder. One study evaluated the efficacy and tolerability of ramelteon in BD type I with manic symptoms and insomnia (53). Twenty-one outpatients were randomized to receive either 8mg/day of ramelteon (N=10) or placebo (N=11) in an 8-week double-blind treatment design.…”
Section: Bipolar Disorder (Bd)mentioning
confidence: 99%